PENDIDIKAN KESETARAAN GENDER DI PONDOK PESANTREN SEBAGAI UPAYA MEMBANGUN PERADABAN BANGSA - Arifah Nurfai (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract This paper aims to describe the notion of gender equality and how gender equality learning can be done in Islamic boarding schools. This study uses a qualitative descriptive analysis method by collecting data from various sources such as scientific journals, websites, and books related to the discourse of gender equality education in Islamic boarding schools. The results showed that; 1) The definition of gender equality education in Islamic boarding schools is the teaching and learning process in an informal Islamic religious institution by ustad/ustadzah discussing in detail the equality of positions between men and women to have equal opportunities in the community 2) Islamic boarding schools can apply gender equality education as follows; First, the Islamic boarding school curriculum must be adapted to the changing times. Second, changing the mindset of female students as being tough, not inferior. Third, explore self-potential by encouraging female students to instil a thirst for knowledge. Fourth, promote the activeness of female students to go directly into the social, political and community spheres. With the pattern of gender equality education in Islamic boarding schools, it is expected to positively impact graduates who have good moral character, are independent, and have achievements. In addition, the existence of this educational concept makes it an opportunity for female students to explore more in improving their soft and hard skills to achieve the progress of the nation and state.   Abstrak Tujuan dari penulisan ini adalah mendeskripsikan pengertian kesetaraan gender dan bagaimana pembelajaran kesetaraan gender yang dapat dilakukan di pondok pesantren. Penelitian ini menggunakan metode analisis deskriptif kualitatif yakni dengan mengumpulkan data dari berbagai sumber seperti jurnal ilmiah, website, dan buku terkait wacana pendidikan kesetaraan gender di pondok pesantren. Hasil penelitian menunjukkan bahwa; 1) Pengertian pendidikan kesetaraan gender di pondok pesantren adalah proses belajar mengajar di suatu lembaga informal agama islam oleh ustad/ustadzah membahas secara detail mengenai persamaan kedudukan antara laki-laki dan perempuan agar memiliki peluang yang setara di lingkungan masyarakat 2) Pondok pesantren dapat menerapkan  pendidikan kesetaraan gender sebagai berikut: Pertama, Kurikulum pondok pesantren harus disesuaikan dengan perubahan zaman. Kedua, Mengubah pola pikir santriwati sebagai makhluk yang tangguh bukan inferior. Ketiga, Menggali potensi diri dengan mendorong santriwati untuk menanamkan jiwa yang haus akan ilmu pengetahuan. Keempat, Mendorong  keaktifan santriwati untuk terjun langsung ke ranah sosial, politik dan masyarakat. Adanya pola pendidikan kesetaraan gender dapat menjadi ajang bagi santriwati untuk lebih berekplorasi dalam meningkatkan softskill dan hardskill yang mereka miliki guna mencapai kemajuan bangsa dan negara.